The Effect of Consumer Trust, Emotional Values, Functional Values and Social Values on Iphone Brand Loyalty in Students of Muhammadiyah University of Bengkulu - Ilahi, Sirat Agus Rahmad; Islamuddin, Islamuddin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
A research that has the formulation of the problem How do Consumer Trust, Emotional Values, Functional Values ​​and Social Values affect Iphone Brand Loyalty in Students of Muhammadiyah University of Bengkulu? The purpose of this study is to find out how the effect of consumer trust, emotional values, functional values ​​and social values ​​on iPhone brand loyalty in Students of Muhammadiyah University of Bengkulu. The sampling technique used was the accidental sampling based on predetermined criteria totaling 100 respondents. The data was collected using the observation, documentation and questionnaires. The data that has been processed was analyzed using the SPSS 24 formula.The hypothesis test with t-test obtained t-count > t-table (2.673> 1.699). The Consumer Trust (X1), Emotional Value (X2), Functional Value (X3) and Social Value (X4) ) has an effect on consumer brand loyalty (Y). This can be seen from the hypothesis test Simultaneously. F-table > F-count (12.749 > 1.850). This is evidenced from the correlation analysis R = 0.802 (80.2%) and almost close to 1. The coefficient of determination is R2 = 0.64.4 or about 64.4% while 35.6% is a contribution of other variables not examined